Evaluating 17 years of latent tuberculosis infection screening in north-west England: a retrospective cohort study of reactivation. Issue 1 (27th July 2017) - Zenner, Dominik; Loutet, Miranda G.; Harris, Ross; Wilson, Stephen; Ormerod, L. Peter
Approximately 72% of tuberculosis (TB) cases in England occur among non-UK born individuals, mostly as a result of reactivation of latent TB infection (LTBI). Programmatic LTBI screening is a key intervention of the TB strategy for England. This article reviews the results of a long-standing LTBI screening initiative in England. A retrospective cohort was created through probabilistic linkage between LTBI screening data and national TB case notifications. Screened persons were followed until they died, became a case, emigrated or until cohort-end. TB incidence rates and rate ratios (IRR) were calculated. 97 out of 1820 individuals screened for LTBI were reported to have active TB. Crude incidence rates among LTBI-positive, treatment-naïve individuals were 4.1 and 2.3 per 100 person-years in the QuantiFERON and tuberculin skin test cohorts, respectively. Among the QuantiFERON cohort, Poisson regression showed that LTBI positivity (IRR 22.6, 95% CI 6.8–74.6) and no chemoprophylaxis increased the probability of becoming a TB case (IRR 0.17, 95% CI 0.05–0.6). We found high TB rates in LTBI-positive, treatment-naïve individuals and a strong association between no treatment and becoming a TB case, demonstrating feasibility and effectiveness of LTBI screening and providing important policy lessons for LTBI screening in England and beyond. Screening follow-up showed high TB rates in LTBI-positive, treatment-naïve individuals and treatment protection http://ow.ly/IUaW30bggkH